2018
DOI: 10.1159/000492815
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Underwater Clip Closure for Large Mucosal Defects after Colorectal Endoscopic Submucosal Dissection

Abstract: Background/Aims: Clip closure of mucosal defects after colorectal endoscopic submucosal dissection (C-ESD) may decrease the incidence of delayed adverse events. The size of the defect to be closed by conventional clip is limited, however, and we sometimes encounter incomplete closure when the defect is located at the flexure. As, theoretically, underwater clip closure (UCC) could achieve complete closure despite these difficult cases, we investigated its feasibility. Methods: We retrospectively analyzed 21 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…88 These techniques are simple, shorten the procedure time, and are cost-effective. However, they seem unfavorable for lesions affecting more than half the circumference 82,87 and lesions in a thick-walled rectum. 82,89 One study revealed a moderate complete closure rate (73% [8/11]) of surgical stitch-based EHS.…”
Section: Colorectal Closure Techniquesmentioning
confidence: 99%
See 3 more Smart Citations
“…88 These techniques are simple, shorten the procedure time, and are cost-effective. However, they seem unfavorable for lesions affecting more than half the circumference 82,87 and lesions in a thick-walled rectum. 82,89 One study revealed a moderate complete closure rate (73% [8/11]) of surgical stitch-based EHS.…”
Section: Colorectal Closure Techniquesmentioning
confidence: 99%
“…9,15,16,78,[82][83][84][85][86][87][88][89][90] The mean defect size, complete closure rate, and procedure time ranged from 31.2 to 40.9 mm, 73% to 100%, and 9.6 to 18.7 min, respectively. Clip-based techniques include mucosal incision, 82 hold-anddrag closure, 83 mucosa-submucosa clips, 86 underwater clip closure, 87 and clip-on-clip closure. 88 These techniques are simple, shorten the procedure time, and are cost-effective.…”
Section: Colorectal Closure Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce the risk of AEs, several studies have suggested prophylactic endoscopic closure of the mucosal defect after colorectal ESD 17–20 . Furthermore, in order to complete closure of large mucosal defects, a number of advanced devices and techniques have been developed 21–30 . Some other studies have indicated that endoscopic closure does not decrease the rate of AEs and may require additional operative time and an increased cost 31–34 .…”
Section: Introductionmentioning
confidence: 99%